Pengelolaan Sumber Daya Manusia (SDM) Yang Efektif Untuk Meningkatkan Kinerja Organisasi - Almadina Nurramadhania (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This journal examines the important role of effective human resource (HR) management in efforts to improve organizational performance. This research involved data analysis and literature review to explore key aspects in HR, such as recruitment, training, development and employee motivation. Apart from that, this journal also discusses the impact of modern technology on HR management. This research shows a strong correlation between achieving company goals and the effectiveness of HR management. These findings have important implications for HR practitioners and organizational leaders in efforts to improve company performance and competitiveness.